Grey Areas in Pakistani Criminal Law: The Missing Safeguards in Arrest Procedures for Vulnerable Accused with Mental Health Conditions and Neurodivergence - Rida Fatima; Fareeha Nayab; Iqra Yaseen (Indonesian Scientific Publication, 2026)
Through a comparative legal review, this paper examines the Pakistani legal framework concerning the protection and rights of the vulnerable population with intellectual disabilities, autism, and other related mental health conditions within the criminal justice system. The paper focuses specifically on the absence of legal safeguards at the point of arrest and during the first 24 hours of custody before the magistrate presentation, a critical period when suspects are most vulnerable to secondary victimisation. Comparative analysis with jurisdictions such as the United Kingdom, the United States, and other countries reveals established mechanisms, including supported decision-making, mandatory police training, and custodial safeguards that protect vulnerable individuals from rights violations. The identified safeguards were systematically compared against the current Pakistani legal framework governing arrest and pre-trial detention. This review produced a structured gap map of Pakistan’s criminal procedure framework, evaluating the absence of enforceable safeguards across four domains: (1) vulnerability identification at arrest, (2) accessible communication of rights, (3) provision of an appropriate adult, (4) coercion prevention during initial custody. The paper concludes that the lack of procedural protections significantly increases the risk of coerced confessions, unreliable testimony, and miscarriages of justice. Urgent reforms are needed, including clearer statutory definitions, harmonisation of laws across provinces, integration of supported decision-making, structured training for law enforcement personnel, and the establishment of independent oversight mechanisms.